2021
DOI: 10.1007/s40140-021-00439-4
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula, a Boon or a Bane for COVID-19 Patients? An Evidence-Based Review

Abstract: Purpose of Review This review instantiates the efficacy and safety of HFNC in the context of COVID-19 pandemic. Recent Findings Globally, the healthcare system is facing an unprecedented crisis of resources due to the 2019 novel coronavirus disease (COVID-19) pandemic. Fever, cough, dyspnea, myalgia, fatigue, and pneumonia are the most common symptoms associated with it. The incidence of invasive mechanical ventilation in ICU patients ranges from 29.1 to 89.9%. Suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Our study found that among patients with acute respiratory failure due to COVID-19 pneumonia who were initially treated with HFNC but subsequently intubated, delayed intubation beyond twenty-four hours was associated with an increased in-hospital mortality. Initial concerns about potential aerosolization of SARS-CoV-2 viral particles and healthcare personnel infection limited the use of HFNC for patients presenting with acute respiratory failure (ARF) due to COVID-19 pneumonia early in the pandemic [ 2 6 ]. However, as infectious risks were better understood, hospital strain escalated, and clinicians gained more experience with HFNC, use of this modality increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that among patients with acute respiratory failure due to COVID-19 pneumonia who were initially treated with HFNC but subsequently intubated, delayed intubation beyond twenty-four hours was associated with an increased in-hospital mortality. Initial concerns about potential aerosolization of SARS-CoV-2 viral particles and healthcare personnel infection limited the use of HFNC for patients presenting with acute respiratory failure (ARF) due to COVID-19 pneumonia early in the pandemic [ 2 6 ]. However, as infectious risks were better understood, hospital strain escalated, and clinicians gained more experience with HFNC, use of this modality increased.…”
Section: Discussionmentioning
confidence: 99%
“…During the peak of the SARS-CoV-2/COVID-19 pandemic, there was a dramatic increase in the demand for advanced respiratory support modalities such as non-invasive positive pressure ventilation (NiPPV), heated and humidified high flow nasal canula (HFNC), as alternatives to invasive mechanical ventilation (IMV) [ 1 ]. In the early phase of the pandemic, concerns about potential aerosolization of SARS-CoV-2 viral particles and healthcare personnel infection limited the use of NiPPV and HFNC for patients presenting with acute respiratory failure (ARF) due to COVID-19 pneumonia [ 2 6 ]. However, during subsequent waves of the pandemic, there was a better appreciation of the transmission risk associated with SARS-CoV-2 hence a gradual and sustained increased in the use of these non-invasive modalities for ARF [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the relevant therapeutic question is whether to employ CPAP or HFNC in certain circumstances and whether some patients with specific characteristics may benefit from one support over another to allocate the appropriate respiratory support to the right patient [40,41]. Indeed, recent trials on CPAP in COVID-19 patients with ARDS, despite lacking a head-to-head design, are improving the selection and stratification criteria and providing further promising data on the safety profile [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The HFNC is another non-invasive strategy that gained popularity during these COVID times. However, its role has been controversial, and there is no consensus in this context for the use of HFNC in COVID-19 pneumonia amongst various eminent organizations [ 35 ]. Considering this, we restricted this systematic review to NIV only.…”
Section: Discussionmentioning
confidence: 99%